Famines during the ʻLittle Ice Ageʼ (1300-1800): socionatural entanglements in premodern societies - Collet, Dominik; Schuh, Maximilian (Springer International Publishing, 2018)
This highly interdisciplinary book studies historical famines as an interface of nature and culture. It will bring together researchers from the natural and social sciences as well as the humanities. With reference to recent interdisciplinary concepts (disaster studies, vulnerability studies, environmental history) it will examine, how the dominant opposition of natural and cultural factors can be overcome. Such an integrated approach includes the "archives of nature" as well as "archives of man". It challenges deterministic models of human-environment interaction and replaces them with a dynamic, historicising approach. As a result it provides a fresh perspective on the entanglement of climate and culture in past societies.
Keywords: Hungersnot; Kleine Eiszeit